Utopias de gênero na literatura brasileira: A Rainha do Ignoto, de Emília Freitas, e Viagem à Santa Vontade, de Maria Godelivie - Gomes, Aline Maire de Oliveira (2016)
By carrying out a survey in the field of Brazilian literature, this work aimed at finding, selecting and analysing speculative works (science fiction, utopias and dystopias) by women authors that could be aligned within a utopian tradition in literature, and that offered subsidies for feminist readings centered upon gender issues. Among the works surveyed, I chose to analise the novel A Rainha do Ignoto (1899), by Emília Freitas, from the state of Ceará; and the cordel poem Viagem à Santa Vontade (2008), by Maria Godelivie, from Paraíba. The former is approached as a gendered separatist utopia and this study also aims at highlighting Freitas´s work from the perspective of Utopian Studies in its interface with a feminist mode of reading; whereas the latter is read as a Cockaigne inflected by feminist contours. In the readings detailed in chapters 1 and 2, I stress the approximations between the literary works focused on, and literary utopias; and, in a very perceptible way, a strong note on the problematization of gender politics as they are metaphorized, in those works, by the figures of separatism and of the land of Cockaigne. For this reading, theorizations by Ildney Cavalcanti (2003), Ruth Levitas (2001), Susana Funck (1993), Zahidé Muzart (1990; 2004; 2006; 2010), Lyman Tower Sargent (1975; 1994), Michel Foucault (1984), for the issues regarding Gender Studies and literary feminist criticismo, Utopian Stdies; Hilário Franco Jr (1998; 1998), Sérgio Buarque de Holanda (2000), about the land of Cockaigne; Adrienne Rich (1979), regarding writing as na act of revision; and Mikhail Bakhtin (1987; 2010) in relation to his theory on carnival and literature, will be taken into consideration. The study offers a contribution to the area of Utopian Studies – with emphasis being placed upon Brazilian texts by women authors – a field which still demands further exploration in the territory of academic research; and also for the construction of critical writings by the Northeastern authors Emília Freitas (about whom there is a considerable amount of criticism) and Maria Godelivie (cordel writer whose work has an incipient critical corpus).